1993
DOI: 10.1093/jis/4.1.33
|View full text |Cite
|
Sign up to set email alerts
|

The Agrarian Economy of Oman (132-280/749-893) in Arabic Sources

Abstract: The effect of age and dietary factors of Anopheles gambiae (Diptera: Culicidae) on the infectivity of natural Plasmodium falciparum parasites was studied. Mosquitoes of various ages (1–3, 4–7 and 8–11 day old) and those fed blood (either single or double meals) and sugar meals were experimentally co-infected with P. falciparum gametocytes obtained from different naturally infected human volunteers. On day 7, midguts were examined for oocyst infection to determine whether mosquito age or diets have significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…aegypti age they become more resistant to a P. gallinaceum infection. More recently, however, Okech et al [ 57 ] found no effect of age on the prevalence of Plasmodium falciparum infections in An. gambiae , although the low infection rates in these experiments (<4 % of the membrane-fed mosquitoes became infected) may have significantly reduced the statistical power of their experiments.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti age they become more resistant to a P. gallinaceum infection. More recently, however, Okech et al [ 57 ] found no effect of age on the prevalence of Plasmodium falciparum infections in An. gambiae , although the low infection rates in these experiments (<4 % of the membrane-fed mosquitoes became infected) may have significantly reduced the statistical power of their experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging adults were fed on 5% glucose, and adults emerging on days 2–4 were pooled in an age-matched group for blood feeding. An age spread this small does not influence infection susceptibility [32]. …”
Section: Methodsmentioning
confidence: 99%
“…Studies on diet effects in mosquito- Plasmodium interactions have lagged behind, but a handful of findings indicate that nutrition can influence mosquito competence [28], [42][46]. These studies have proven difficult to reconcile however, as the competence and immune response of food-deprived larvae or adult mosquitoes was reported to be higher in some instances [28], [43], [46] but lower in others [42], [44] ( Table 1 ). It remains unclear whether these discrepancies are due to species-specific differences or to the type and degree of nutritional stress.…”
Section: Non-genetic Influences On Mosquito Competencementioning
confidence: 99%
“…gambiae to melanize foreign entities was reduced in old females [64], recent findings revealed no age effect on An. gambiae competence for fungi [65] or P. falciparum [44].…”
Section: Non-genetic Influences On Mosquito Competencementioning
confidence: 99%